Awareness, prevalence and risk burden of cataract among adults in IDO/OSI local government area, a rural community of Ekiti state, southwest Nigeria - Adeniyi, Makinde A.; Adewoye, RaRasaq K.; Popoola, Gbenga O.; Aderukuola, Babatunde; Ibrahim, Azeez O.; Azees, Ayotunde S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Cataract is characterized by lens opacity, making images look blurred and hazy. It causes increased light sensitivity, decreased vision at night, and seeing double images, leading to total blindness. The WHO also estimates that cataract blindness will reach 40 million by 2025 due to ageing population and longer life expectancy. Developing countries, including Sub-Saharan Africa have the highest number of people who are blind due to cataract. This study aims to determine the awareness, prevalence and risk burden of cataract among adults in Ido/Osi LGA, a rural community of Ekiti State. Methods: This is a descriptive cross-sectional study. The estimated sample size is 361 and a multi stage sampling technique was used. Data collection was through ophthalmic examinations and questionnaires which were analyzed using SPSS version 25.0. Results: The mean age of respondents was 54.94±11.17. Most respondents, 287 (79.5%), had a good awareness of cataracts. The prevalence of cataract in this study is 3.9%. Cataract significant Visual Acuity was found in 49 (13.5%) of the respondents. Age (<0.001), visual impairment (<0.001), hypertension (<0.001) and diabetes mellitus (0.003) were the factors associated with having cataracts. Conclusions: Intersectorial collaboration, health education through the mass media, evidenced based policies and research will help reduce the prevalence of cataract.